Robots : facts behind the fiction - Chester, Michael (New York : Macmillan ; London : Collier Macmillan, 1983)
Describes the development of robots, which paralleled that of computers, how robots work, and the many functions they fulfill, with emphasis on robots built by amateur hobbyists.
Includes index.
Bibliography: p. 85-86.
Keywords: Robotics -- Juvenile literature; Robots